ANALISIS PELAKSANAAN STRATEGI REFORMASI BIROKRASI PADA LEMBAGA PEMERINTAH DAERAH: STUDI PADA SEKRETARIAT DAERAH KABUPATEN LUWU UTARA - Said, Rusdin; Wahyuti, Sri; RT, Moh. Baso (Saraq Opat: Jurnal Administrasi Publik, 2023)
Bureaucratic reform is a change implemented within a public institution environment in accordance with statutory limitations. the concept of “bureaucratic reform” refers to quality improvement. This study looks at how bureaucratic reform initiatives are implemented in local government organizations, especially the Regional Secretariat Office of North Luwu Regency. The problem in this study is that the Regional Government of North Luwu Regency, especially in the regional secretariat office, has not implemented bureaucratic reform properly. The rule that is used as the basis for this study is MENPAN Regulation No.PER/15/M.PAN/7/2009, which includes internal control, strategic direction, change management, system management, organization management, and management systems for human resources. This type of research uses qualitative data collection methods such as interviews, documentation studies, and observations to gather information. The findings of the study are: The North Luwu Regency Government has established the main tasks and functions of assisting the implementation of bureaucratic reform through the Regional Secretariat. In particular, the implementation of the bureaucratic reform strategy by the Secretariat of North Luwu Regency has not been successful or not ideal, especially in nine areas, namely changes in strategic direction, changes in governance policies, system governance, and organizational governance, management, management management system management, human resource management, organizational unit strengthening, regional regulations, and internal control.